Independent signaling by Drosophila insulin receptor for axon guidance and growth - Li, Caroline R.; Guo, Dongyu; Pick, Leslie (Frontiers in Physiology, 2014)
The Drosophila insulin receptor (DInR) regulates a diverse array of biological processes including growth, axon guidance, and sugar homeostasis. Growth regulation by DInR is mediated by Chico, the Drosophila homolog of vertebrate insulin-receptor-substrate proteins IRS1-4. In contrast, DInR regulation of photoreceptor axon guidance in the developing visual system is mediated by the SH2-SH3 domain adaptor protein Dreadlocks (Dock). In vitro studies by others identified five NPXY motifs, one in the juxtamembrane region and four in the signaling C-terminal tail (C-tail), important for interaction with Chico. Here we used yeast two-hybrid assays to identify regions in the DInR C-tail that interact with Dock. These Dock-binding sites were in separate portions of the C-tail from the previously identified Chico-binding sites. To test whether these sites are required for growth or axon guidance in whole animals, a panel of DInR proteins, in which the putative Chico and Dock interaction sites had been mutated individually or in combination, were tested for their ability to rescue viability, growth, and axon guidance defects of dinr mutant flies. Sites required for viability were identified. Unexpectedly, mutation of both putative Dock binding sites, either individually or in combination, did not lead to defects in photoreceptor axon guidance. Thus, either sites also required for viability are necessary for DInR function in axon guidance and/or there is redundancy built into the DInR/Dock interaction such that Dock is able to interact with multiple regions of DInR. We also found that simultaneous mutation of all 5 NPXY motifs implicated in Chico interaction drastically decreased growth in both male and female adult flies. Mutation of these 5 NPXY motifs did not affect photoreceptor axon guidance, showing that different sites within DInR control growth and axon guidance.